Letter from Samuel Durborow to James Curtis Booth - Durborow, Samuel (1884)
Samuel Durborow, of the Philadelphia Protestant Episcopal City Mission, writes to James Curtis Booth (1810-1888) with thanks for his donation.
Keywords: Booth, James Curtis, 1810-1888